Phenotypic and Functional Changes of Endothelial and Smooth Muscle Cells in Thoracic Aortic Aneurysms - Anna Malashicheva; Daria Kostina; Aleksandra Kostina; Olga Irtyuga; Irina Voronkina; Larisa Smagina; Elena Ignatieva; Natalia Gavriliuk; Vladimir Uspensky; Olga Moiseeva; Jarle Vaage; Anna Kostareva (International Journal of Vascular Medicine)
Thoracic aortic aneurysm develops as a result of complex series of events that alter the cellular structure and the composition of the extracellular matrix of the aortic wall. The purpose of the present work was to study the cellular functions of endothelial and smooth muscle cells from the patients with aneurysms of the thoracic aorta. We studied endothelial and smooth muscle cells from aneurysms in patients with bicuspid aortic valve and with tricuspid aortic valve. The expression of key markers of endothelial (CD31, vWF, and VE-cadherin) and smooth muscle (SMA, SM22α, calponin, and vimentin) cells as well extracellular matrix and MMP activity was studied as well as and apoptosis and cell proliferation. Expression of functional markers of endothelial and smooth muscle cells was reduced in patient cells. Cellular proliferation, migration, and synthesis of extracellular matrix proteins are attenuated in the cells of the patients. We show for the first time that aortic endothelial cell phenotype is changed in the thoracic aortic aneurysms compared to normal aortic wall. In conclusion both endothelial and smooth muscle cells from aneurysms of the ascending aorta have downregulated specific cellular markers and altered functional properties, such as growth rate, apoptosis induction, and extracellular matrix synthesis.